Paulus als Erzähler?: Eine narratologische Perspektive auf die Paulusbriefe - Heilig, Christoph (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2020)
In recent Pauline research, the critical importance of implicit narratives for understanding the apostle’s Epistles gained importance. The study examines this in a critical analysis using narrative theory and text linguistics. Heilig’s text analysis lines out a new narratological approach to Pauline exegesis